College higher education in England 1944-66 and 1997-2010 (UCL Press, 2016)
As a contribution to the history of higher education in English further education colleges, two policy episodes are sketched and compared. Both periods saw attempts to expand courses of higher education outside the universities. In the first, ahead of policies to concentrate non-university higher education in the strongest institutions, efforts were made after 1944 to recognize a hierarchy of colleges, with separate tiers associated with different volumes and types of advanced further education. In the second, soon after unification of the higher education sector at the beginning of the 1990s, all colleges in the further education sector were encouraged to offer higher-level programmes and qualifications, with a reluctance or refusal on the part of central government to plan, coordinate, or configure this provision. The two episodes highlight very different assumptions about what types of institutions should be involved in what kinds of higher education. They are a reminder too of how short is the policy memory on higher education within modern-day governments and their agencies.